Intraepithelial haemorrhage of the oesophagus: a terminal event in haematological disorders. Issue 11 (November 1998) - Shimizu, M; Matsumoto, T; Hirokawa, M; Monobe, Y; Iida, M; Manabe, T
Abstract : AIMS: To investigate the clinicopathological findings in cases with intraepithelial haemorrhage of the oesophagus (IHO). METHODS: Necropsy records and the histopathology findings in the oesophagus were reviewed for the period 1990 to 1995. Six cases (0.7%) of IHO were found among 919 necropsy cases. Clinical records of these patients and gross and microscopic slides were reviewed in detail. RESULTS: The ages of the IHO cases ranged from 42 to 82 years (average 68 years), with a male to female ratio of 1:2. All cases had underlying haematological disorders with thrombocytopenia, but disseminated intravascular coagulation was not evident in any case. Macroscopically, solitary (two cases) or multiple (four cases) haemorrhagic lesions ranging from 6 to 79 mm in size were identified within the distal oesophagus. Microscopically, there was no inflammatory infiltration, destruction of red blood cells, or submucosal scar formation. CONCLUSIONS: IHO seems to occur shortly before death as a terminal event in haematological disorders. Based on these observations, the term "terminal IHO" can be suggested for this type of oesophageal lesion.